APLIKSI PENGOLAHAN DATA PELAYANAN KESEHATAN MASYARAKAT BERBASIS WEB PADA KELURAHAN KEMBANG SARI - nur, amri muliawan; fathurahman, imam (Fakultas Teknik Universitas Hamzanwadi, 2020)
Poskesdes (Village Health Post) Kembang Sari provides health services to rural communities so that the realization of a healthy, responsive community capable of preventing and overcoming health problems. Patient data collection at the poskesdes kembang sari is still done manually which results in frequent errors in recording patient data. Especially, at the time of data compilation it will be made in the form of reports. To overcome this problem, the authors propose to build and design an application that can help health workers in making patient data reports. The method used in this system is to use the web as an access medium using PHP and MySQL programming languages. In the design, this system uses flow map, context diagrams and database tables. In conclusion, this application can help and facilitate village health service workers in the Kembang Sari Village in entering data, verifying, making reports about patient data more optimallyDOI : 10.29408/jit.v3i2.2319